2017
DOI: 10.1080/10410236.2017.1339371
|View full text |Cite
|
Sign up to set email alerts
|

“You See Yourself Like in a Mirror”: The Effects of Internet-Mediated Personal Networks on Body Image and Eating Disorders

Abstract: -Body image issues associated with eating disorders consist of attitudinal and perceptual components: individuals' dissatisfaction with body shape or weight, and inability to correctly assess body size. While prior research has mainly explored social pressure from media, fashion, and advertising, we aim to uncover how personal networks, also encompassing internet-mediated interactions, bear upon body image. We estimate these effects with data from a survey of users of websites on eating disorders, including in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 55 publications
3
19
1
Order By: Relevance
“…For example, specialty communities that emerge in forums such as PatientsLikeMe may be very influential because they offer a place where people can share information about extremely important and relevant topics among members of a specific community. For example, in our recent study (66), researchers showed that individuals' concerns about their weight and appearance are significantly influenced by both their online and offline social networks and that this influence varies by body-mass index.…”
Section: Internet Mediatedmentioning
confidence: 94%
“…For example, specialty communities that emerge in forums such as PatientsLikeMe may be very influential because they offer a place where people can share information about extremely important and relevant topics among members of a specific community. For example, in our recent study (66), researchers showed that individuals' concerns about their weight and appearance are significantly influenced by both their online and offline social networks and that this influence varies by body-mass index.…”
Section: Internet Mediatedmentioning
confidence: 94%
“…BIG allows individuals to select male silhouettes with varying degrees of both muscle mass and body fat level, which are essential components of body image disturbances in men. Figure-rating scales such as BIG are highly correlated with self-reported body mass index (BMI [37];), and can detect body-related attitudinal and perceptual disturbances including body dissatisfaction and body image distortions [52]. This measure consists of 30 male silhouettes with varying levels of muscle and body fat, displayed in a grid.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has shown that commercials and standards of physical appearance and body image promoted by the mass media usually affect how appealing body image should look like (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The influence produced by media, advertising, websites, and personal networks is examined (18). However, not many studies determine the strength of the interrelationship between body image standards presented by the mass media and restrictive and bulimic behavior in a homogeneous population of women and men in term of age, Body Mass Index (BMI), and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%